2022
DOI: 10.1111/raq.12762
|View full text |Cite
|
Sign up to set email alerts
|

Fish disease and intestinal microbiota: A close and indivisible relationship

Abstract: The gut microbiota is currently one of the most studied 'organs' in animals, and fish are no exception. A complex diversity of microbes, including bacteria, archaea, yeast and fungus, constitute the gut microbiota, creating a complex interaction with their host and accomplishing multiple beneficial functions, such as food digestion, nutrient absorption, immune system, endocrine and stress response. The microbiotapathogen interaction protects the host by mounting colonization resistance, competing for nutrients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 243 publications
(524 reference statements)
0
16
0
Order By: Relevance
“…At the genus level, the greatest abundance (41–52%) comprised of Cetobacterium in all treatments. Although Cetobacterium abundance was lower in the fish fed the ANIMAL diet, this genus is commonly present in freshwater fish microbiota [ 43 , 46 , 49 ] and is known to have a high capacity to produce vitamin B12 and other compounds such as organic acids and enzymes [ 50 ]. In relation to the ANIMAL treatment, we observed a decrease in the abundance of several genus species within the Proteobacteria phylum and an increase in the genus Paludibacter and family Bacteriodales within the Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the genus level, the greatest abundance (41–52%) comprised of Cetobacterium in all treatments. Although Cetobacterium abundance was lower in the fish fed the ANIMAL diet, this genus is commonly present in freshwater fish microbiota [ 43 , 46 , 49 ] and is known to have a high capacity to produce vitamin B12 and other compounds such as organic acids and enzymes [ 50 ]. In relation to the ANIMAL treatment, we observed a decrease in the abundance of several genus species within the Proteobacteria phylum and an increase in the genus Paludibacter and family Bacteriodales within the Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that in our study, apart from Paludibacter sp., Agrobacterium sp., and Propionibacterium acnes , the most correlated microbiota had low abundance. Lower-abundance taxa are normally not identified in core microbiomes; however, studies have shown a strong impact on the host’s health [ 49 , 55 ]. As an example, in invertebrate animals, such as termites, low-abundance microorganisms shift with dietary factors and drive the whole BACTERIAL community, leading to a higher resistance [ 50 ], whereas in humans several keystone low-abundance microorganisms are pathobionts associated with diseases [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review is only focused on the bacterial component of fish microbiome, as it is the best studied. However, it will be important to understand whether the patterns identified here also occur in other components such as the mycobiome, which is often neglected but very important for fish homeostasis 153 …”
Section: Discussionmentioning
confidence: 99%
“…A. hydrophila , Aeromonas caviae , Aeromonas veronii , and Aeromonas salmonicida were detected as ARG-carrying pathogens and are fairly resilient pathogens. They can produce enterotoxins, posing a significant challenge to host microbiota stability and resilience [ 58 , 59 ]. Such hosts can spread ARGs to confer resistance to antibiotics via horizontal gene transfer and mutational events [ 60 , 61 ], resulting in the spread of ARB and increasing the economic burdens in aquaculture [ 62 ].…”
Section: Discussionmentioning
confidence: 99%